2017
DOI: 10.1111/evo.13166
|View full text |Cite
|
Sign up to set email alerts
|

Variation of anal fin egg-spots along an environmental gradient in a haplochromine cichlid fish

Abstract: Male secondary sexual traits are targets of inter-and/or intrasexual selection, but can vary due to a correlation with life-history traits or as by-product of adaptation to distinct environments. Trade-offs contributing to this variation may comprise conspicuousness towards conspecifics versus inconspicuousness towards predators, or between allocating resources into coloration versus the immune system. Here, we examine variation in expression of a carotenoid-based visual signal, analfin egg-spots, along a repl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
34
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 24 publications
(39 citation statements)
references
References 93 publications
(188 reference statements)
3
34
2
Order By: Relevance
“…; Theis et al. ). Accordingly, in BPMB species both males and females were expected to allocate more resources into life‐history traits and, thus, to have a more potent immune system, compared to MMB species.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…; Theis et al. ). Accordingly, in BPMB species both males and females were expected to allocate more resources into life‐history traits and, thus, to have a more potent immune system, compared to MMB species.…”
Section: Discussionmentioning
confidence: 98%
“…We hypothesized an existing resource allocation trade-off between investing into parental care (in our case MB) versus resource allocation into life-history traits including the immune system (Stearns 1989;Santos and Nakagawa 2012;Carlton et al 2014;Theis et al 2017). Accordingly, in BPMB species both males and females were expected to allocate more resources into life-history traits and, thus, to have a more potent immune system, compared to MMB species.…”
Section: Parental Care and The Immune Systemmentioning
confidence: 99%
“…Astatotilapia burtoni has previously been reported to occur in habitats such as marshy marginal ponds or lagoons, always in association with inflowing rivers (Fernald & Hirata, 1977a). Our own previous work has challenged this view in that we investigated many lake populations and showed that lake fish are phenotypically and ecologically distinct from river fish (Egger et al., 2017; Theis et al., 2014, 2017). At Crocodile Island (CRO), which is situated about 1.2 km away from the closest (southeastern) shoreline, A. burtoni are found in a water depth of 5–8 m, indicating that A. burtoni can survive and maintain populations in a proper lake habitat.…”
Section: Discussionmentioning
confidence: 99%
“…We used a lake population from the estuary of the Kalambo River (KaL) on the east coast of Lake Tanganyika, a lake population from the west coast (NdL), and a genetically divergent river population from the west coast – the Lufubu River (LfR) (referred to as Lf2 in Theis et al. , ; Egger et al. ; Pauquet et al.…”
mentioning
confidence: 99%
“…1) is an excellent model to study the early phases of adaptive divergence. Lake and river ecotypes of A. burtoni show habitat specific adaptations, despite varying levels of genetic differentiation among them (Theis et al 2014;Egger et al 2017;Pauquet et al 2018). Adjacent lake and river environments differ in both abiotic and biotic conditions including water chemistry, habitat structure, and prey composition (Theis et al 2014).…”
mentioning
confidence: 99%